Upaya Peningkatan Hasil Belajar Pendidikan Agama Islam pada Materi Salat dan Zikir melalui Penggunaan Gamma : Presentations and Slide Decks with AI di Kelas VII SMP Negeri 2 Padang Tualang - Nur Rafi’a Hafiza (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research focuses on improving the learning outcomes of class VII students in Islamic Religious Education (PAI) subjects, especially in prayer and dhikr material, which often experience obstacles due to ineffective conventional teaching methods. To overcome this problem, research was carried out using the Classroom Action Research (PTK) method involving 30 students, carried out in two cycles with planning, implementation, observation and reflection stages. The use of AI-based learning media Gamma: Presentations and Slide Decks is expected to increase student involvement and make understanding the material easier. The research results showed that in cycle I, 76.6% of students achieved the minimum completeness criteria (KKM), and this figure increased significantly to 93.33% in cycle II. These findings indicate that the implementation of Gamma is not only effective in improving student learning outcomes, but also creates a more interactive and interesting learning experience, thereby making a positive contribution to the quality of religious education at the junior high school level.